Optimization of Fin Geometry for Condensation on Integral Fin Tubes - Dandajeh, H. A.; Sanusi, Y. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This paper reports an optimization aimed at verifying the accuracy of a semi-empirical condensation heat transfer model in calculating the enhancement ratio of a rectangular- finned tube. Three condensing fluids (ethylene glycol, refrigerant-R113 and steam) and three tube materials (copper, brass and bronze) were used to evaluate the response of the model at different fluid properties. Optimum tube geometries (diameter, fin thickness, height and spacing) were calculated and later compared with those geometries of a real condenser. The verification was achieved by comparing the condensation results of the model based on numerical calculations using Excel spread sheet with an established experimental data from the measurements of condensation heat transfer. The optimization results showed that the model accurately predicted the observed trends in the experimental data for the condensing fluids of steam, R113 and ethylene glycol. Condensation of refrigerant-R113 on copper tube material was found to be the best predicted model. Calculated optimum fin spacing for steam as a condensing fluid corresponded reasonably to those of a real condenser. Optimum fin spacing increased with increased surface tension.